2019
DOI: 10.1177/2470547018821496
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Alarm System and Subliminal Threat Presentation in Posttraumatic Stress Disorder: Neuroimaging of the Midbrain and Cerebellum

Abstract: Background: The innate alarm system, a network of interconnected midbrain, other brainstem, and thalamic structures, serves to rapidly detect stimuli in the environment prior to the onset of conscious awareness. This system is sensitive to threatening stimuli and has evolved to process these stimuli subliminally for hastened responding. Despite the conscious unawareness, the presentation of subliminal threat stimuli generates increased activation of limbic structures, including the amygdala and insula, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 116 publications
3
40
0
Order By: Relevance
“…Deep-layer neuronal circuits that control innate and learned reflexive responses as well as arousal [99][100][101] are becoming increasingly important in the neurobiological conceptualization of PTSD. 1,2,[14][15][16]18,19,[65][66][67][99][100][101][102][103] Crucially, these fundamental neuronal circuits determine the general arousal state of the organism, laying the foundation for reflexive actions. 26 The present investigation provides novel evidence that as compared to both control subjects and individuals with PTSD, participants with PTSDþDS showed stronger rsFC of the PPN with the amygdala, the parahippocampal gyrus, the anterior cingulate cortex, and the ventromedial prefrontal cortex.…”
Section: Ppn Rsfc With Brain Regions Involved In Innate Threat and Armentioning
confidence: 99%
See 1 more Smart Citation
“…Deep-layer neuronal circuits that control innate and learned reflexive responses as well as arousal [99][100][101] are becoming increasingly important in the neurobiological conceptualization of PTSD. 1,2,[14][15][16]18,19,[65][66][67][99][100][101][102][103] Crucially, these fundamental neuronal circuits determine the general arousal state of the organism, laying the foundation for reflexive actions. 26 The present investigation provides novel evidence that as compared to both control subjects and individuals with PTSD, participants with PTSDþDS showed stronger rsFC of the PPN with the amygdala, the parahippocampal gyrus, the anterior cingulate cortex, and the ventromedial prefrontal cortex.…”
Section: Ppn Rsfc With Brain Regions Involved In Innate Threat and Armentioning
confidence: 99%
“…5,[46][47][48][49][50][51][52][53][54][55][56] Importantly, recent studies emphasize sensitization, particularly in innate threat processing-related brain regions in PTSD, where the presentation of subliminal threat cues elicited stronger activation in the brainstem, the midbrain, the amygdala, and the parahippocampal gyrus in individuals with PTSD as compared to healthy trauma-and non-trauma-exposed controls. 5,[57][58][59][60][61][62][63] Despite emerging evidence of altered states of arousal, and the sensitization of innate threat processing in PTSD during symptom provocation and resting state, 1,2,5,43,44,[57][58][59][60][61][62][64][65][66][67] research examining connectivity of the RAS to subcortical and to cortical brain structures remains in its nascent stages. Accordingly, we sought to delineate resting state functional connectivity (rsFC) patterns of a main component of the RAS, the pedunculopontine nuclei (PPN), 39,[68][69][70][71][72][73][74]…”
Section: Introductionmentioning
confidence: 99%
“…The analyses discussed in this article are novel; however, the data generated on this sample are analyzed in our other published works. 27,29,48,49 The exclusion criteria for participation in the study included incompatibilities with the scanning requirements, previous neurologic and development illness, comorbid schizophrenia or bipolar disorder, alcohol or substance abuse within six months prior to scanning, a history of head trauma, or pregnancy during the time of the scan. Diagnoses were determined using the Clinician Administered PTSD Scale (CAPS) 50 and confirmed by a Structured Clinical Interview for DSM-IV Axis-I disorders.…”
Section: Methods Participantsmentioning
confidence: 99%
“…20 Notably, several structures associated with the IAS display overactivation during the presentation of fear-or trauma-related material in PTSD, including the amygdala, [21][22][23] the parahippocampal gyrus, 24,25 the lower brainstem, 26,27 and the PAG. 26,28,29 Critically, this pattern of neural response emerges under conditions of subliminal and of supraliminal presentation. 21,26,27 In particular, a recent study by Terpou et al 29 revealed a cluster of significantly greater activation of the PAG, as compared to controls, in participants with PTSD during the subliminal presentation of trauma-related word stimuli-to which the present report builds on these findings.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation